1978
DOI: 10.1083/jcb.76.2.418
|View full text |Cite
|
Sign up to set email alerts
|

Cytological events involved in glycoprotein synthesis in cellular and syncytial trophoblast of human placenta. An electron microscope autoradiographic study of [3H]galactose incorporation.

Abstract: Electron microscope autoradiography was used to study glycoprotein synthesis in cellular trophoblast (cytotrophoblast) and syncytial trophoblast of term human placental villi incubated in vitro with D-[1-aH]galactose ([SH]gal). Autoradiographs were analyzed using the hypothetical grain analysis of Blackett and Parry (1973. J. Cell Biol. 57:9-15 [aH]gal incorporated into cytotrophoblast during the pulse incubation remained intracellular through the duration of the experiment. There was little autoradiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…No plateau in tissue incorpora tion of 3H-galactose was observed. Tissues heated prior to incubation or incubated at 4 °C with UDP-3H-gal showed the absence of nonspecific adsorption of radioactivity to tissue indicating the need for an active enzyme system to have significant TCA-precipitable radioactivity in incubated tis-suc; (3) tissue incubated with 'H-gal contained significantly lower levels of TCA-precipitable radioactivity than tissue incubated with UDP-'H-gal at the same specific activity; (4) extending the autoradiographic studies pres ented in this paper, an electron-microscopic autoradiographic study of 'H-galactose incorporation into trophoblast has shown the galactosyltrans férase activity located in the cytoplasm of syncytial trophoblast to be ex tremely low, especially in comparison to that present in cytotrophoblast ( 12). It thus appears that !H-gal was utilized predominantly by intracellular glycosyltransfcrases of cytotrophoblast while the sugar of UDP-3H-gal (in the presence of 'H-gal) was incorporated into acceptors at the microvillous surface of syncytium.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…No plateau in tissue incorpora tion of 3H-galactose was observed. Tissues heated prior to incubation or incubated at 4 °C with UDP-3H-gal showed the absence of nonspecific adsorption of radioactivity to tissue indicating the need for an active enzyme system to have significant TCA-precipitable radioactivity in incubated tis-suc; (3) tissue incubated with 'H-gal contained significantly lower levels of TCA-precipitable radioactivity than tissue incubated with UDP-'H-gal at the same specific activity; (4) extending the autoradiographic studies pres ented in this paper, an electron-microscopic autoradiographic study of 'H-galactose incorporation into trophoblast has shown the galactosyltrans férase activity located in the cytoplasm of syncytial trophoblast to be ex tremely low, especially in comparison to that present in cytotrophoblast ( 12). It thus appears that !H-gal was utilized predominantly by intracellular glycosyltransfcrases of cytotrophoblast while the sugar of UDP-3H-gal (in the presence of 'H-gal) was incorporated into acceptors at the microvillous surface of syncytium.…”
Section: Discussionsupporting
confidence: 51%
“…The present study was undertaken to explore a possible mechanism of surface coat synthesis and/ 268 N elson Endf.rs/K ing or repair. The syncytial trophoblast has previously been shown to have minimal intrasyncytial galactosyltransférase activity at term [12]. The bio chemical and autoradiographic study reported here shows that syncytial trophoblast is capable of resynthesizing cleaved galactose moieties in the glycocalyx without dependence on cytoplasmically located galactosyltransferases.…”
Section: Introductionmentioning
confidence: 53%
“…First, the method takes into account the actual shapes and sizes of subceUular components observed in the set of autoradiographs being analyzed and thus avoids the need for constructing theoretical models of subcellular structures in order to take into account "cross-fire" effects of tritium emissions that cause grains to develop over organelles that are nonradioactive. An example of the usefulness of this aspect of the analysis is the fact that the grains overlying the compartment RER/ Mit could not be assigned to RER only in this study but could be assigned to RER in the following study of glycoprotein synthesis in trophoblast (41). The results of other autoradiographic (1,15) and biochemical (35,62) studies of a variety of tissues, including human placenta (38), are consistent with mitochondrial protein synthesis.…”
Section: Use Of Hypothetical Grain Analysismentioning
confidence: 56%
“…by RER are destined for secretion, as illustrated in the following study of cytotrophoblast (41) and by other investigators studying liver cells (2,3,21). The constitutive proteins most likely contribute to the process of division and/or differentiation of cytotrophoblast.…”
Section: Synthesis Of Proteins In Cytotrophoblastmentioning
confidence: 90%
See 1 more Smart Citation